Lower Ventromedial Prefrontal Cortex Glutamate Levels in Patients With Obsessive–Compulsive Disorder - Batistuzzo, Marcelo C.; Sottili, Bruna A.; Shavitt, Roseli G.; Lopes, Antonio C.; Cappi, Carolina; de Mathis, Maria Alice; Pastorello, Bruno; Diniz, Juliana B.; Silva, Renata M. F.; Miguel, Euripedes C.; Hoexter, Marcelo Q.; Otaduy, Maria C. (Frontiers in Psychiatry, 2021)
Background: Recent studies using magnetic resonance spectroscopy (1H-MRS) indicate that patients with obsessive–compulsive disorder (OCD) present abnormal levels of glutamate (Glu) and gamma aminobutyric acid (GABA) in the frontal and striatal regions of the brain. These abnormalities could be related to the hyperactivation observed in cortico-striatal circuits of patients with OCD. However, most of the previous 1H-MRS studies were not capable of differentiating the signal from metabolites that overlap in the spectrum, such as Glu and glutamine (Gln), and referred to the detected signal as the composite measure—Glx (sum of Glu and Gln). In this study, we used a two-dimensional JPRESS 1H-MRS sequence that allows the discrimination of overlapping metabolites by observing the differences in J-coupling, leading to higher accuracy in the quantification of all metabolites. Our objective was to identify possible alterations in the neurometabolism of OCD, focusing on Glu and GABA, which are key neurotransmitters in the brain that could provide insights into the underlying neurochemistry of a putative excitatory/inhibitory imbalance. Secondary analysis was performed including metabolites such as Gln, creatine (Cr), N-acetylaspartate, glutathione, choline, lactate, and myo-inositol. Methods: Fifty-nine patients with OCD and 42 healthy controls (HCs) underwent 3T 1H-MRS in the ventromedial prefrontal cortex (vmPFC, 30 × 25 × 25 mm3). Metabolites were quantified using ProFit (version 2.0) and Cr as a reference. Furthermore, Glu/GABA and Glu/Gln ratios were calculated. Generalized linear models (GLMs) were conducted using each metabolite as a dependent variable and age, sex, and gray matter fraction (fGM) as confounding factors. GLM analysis was also used to test for associations between clinical symptoms and neurometabolites. Results: The GLM analysis indicated lower levels of Glu/Cr in patients with OCD (z = 2.540; p = 0.011). No other comparisons reached significant differences between groups for all the metabolites studied. No associations between metabolites and clinical symptoms were detected. Conclusions: The decreased Glu/Cr concentrations in the vmPFC of patients with OCD indicate a neurochemical imbalance in the excitatory neurotransmission that could be associated with the neurobiology of the disease and may be relevant for the pathophysiology of OCD.